Roma in an Expanding Europe : Breaking the Poverty Cycle - Ringold, Dena (Washington, DC: World Bank, 2013)
This publication brings together original sociological research, evaluations of programs, and the first comparative cross-country household survey on ethnicity and poverty. It finds that Roma poverty is multi-faceted and can only be addressed by a comprehensive policy approach that attends to all dimensions of Roma social exclusion. It proposes an inclusive policy approach which would expand and promote Roma involvement and participation in mainstream society, while maintaining cultural and social identity and autonomy. Policy mechanisms include those which make existing policies more accessible to Roma and identifying areas where targeted initiatives are needed.